The causal relationship model influencing innovative effectiveness of SMEs to support the enabling BCG economy in Thailand - Witheeprai, Wilas; Praneetpolgrang, Prasong; Thipbharos, Piyavit; Wongkitisopon, Prasan; Pattaramaetakul, Chanapatt (Edelweiss Applied Science and Technology, 2025)
There is currently no clear evidence on the study of the role of Knowledge-based dynamic capabilities (KBDC) and Open Innovation (OI) on Innovative Effectiveness (IE) in the context of Small and Medium Enterprises (SMEs) in Thailand. Therefore, the objective of this study is to investigate the relationship patterns between these variables using quantitative research methods, analyzing structural equation modeling with Jamovi version 2.6.44 software, based on a sample of 321 Thai SME personnel. The results demonstrate the positive impact of KBDC on both OI and IE. Furthermore, OI not only has a direct influence on IE but also serves as a partial mediator in the relationship between KBDC and IE. This study has practical implications that emphasize the importance of developing SMEs’ knowledge management capabilities to adapt to diverse situations, leading to the development of innovations that respond to change. Additionally, it highlights the importance of seeking and utilizing external players through the OI strategy, which will encourage SMEs to combine their company’s knowledge with external knowledge to position themselves for innovation development.